Pregnancy after the age of 35: obstetrics results in the material from the Department of Obstetrics of Collegium Medicum in Bydgoszcz (Menopause Review/Przegląd Menopauzalny, 2012)

(untitled) - Jagielska, Iwona; Kazdepka-Ziemińska, Anita; Janicki, Radosław; Żołnieżewicz, Krzysztof; Grabiec, Marek
Objectives: For the last few decades, a trend towards late motherhood has been noticeable. Pregnant women after 35 years of age are considered to be predisposed to a high risk of perinatal complications. Design : The aim of this study was to analyze the course of pregnancy and delivery, and the newborn status in women over 35 years of age. Materials and methods: The study included women over 35 years of age who gave birth at the Department of Obstetrics in the period from 1 January to 31 December 2010; it evaluated the incidence of pregnancy complications, the way of its completion, the weight of the newborn and Apgar. The results were compared among the groups classified according to age and parity. Statistical analysis was performed using the statistical program STATISTICA 9.0 StatSoft®. Results : During this period, women over 35 years of age accounted for 4.9% and over 40 – 1.13% of all women in labor. Almost two thirds of women had secondary or higher education and came from urban areas. A higher percentage of cesarean sections was found in women over 40 years of age. The most common complications were preterm labor and gestational diabetes. The status of newborns evaluated at 3 minute Apgar scores did not differ in the compared groups, and the average score was 8.82. Over 70% of pregnancies were completed after the 37th week. Conclusions : With age, an increasing number of cesarean sections were performed. Late mothers primarily are women aged 35-39 years, coming from urban areas and better educated (p < 0.05). The most common complications reported include preterm delivery and gestational diabetes. The maternal age and parity did not affect the clinical status of the newborn.